Human and Machine Perception 3 Thinking, Deciding, and Acting - Cantoni, Virginio; di Gesù, Vito; Setti, Alessandra; Tegolo, Domenico (Springer US, 2001)
The following are the proceedings of the Fourth International Workshop on Human and Machine Perception held in Palermo, Italy, on June 20 -23, 2000, under the auspices of three Institutions: the Cybernetic and Biophysics Group (GNCB) of the Italian National Research Council (CNR) and the two Inter-Department Centers of Cognitive Sciences of Palermo and Pavia University respectively. A broad spectrum of topics are covered in this series, ranging from computer perception to psychology and physiology of perception. The theme of this workshop on Human and Machine Perception was focused on Thinking, Deciding, and Acting. As in the past editions the final goal has been the analysis and the comparison of biological and artificial solutions. The focus of the lectures has been on presenting the state-of-the-art and outlining open questions. In particular, they sought to stress links, suggesting possible synergies between the different cultural areas. The panel discussion has been conceived as a forum for an open debate, briefly introduced by each panelist, and mainly aimed at deeper investigation of the different approaches to perception and strictly related topics. The panelists were asked to prepare a few statements on hot-points as a guide for discussion. These statements were delivered to the participants together with the final program, for a more qualified discussion